Rebounding Ability of Weaver Ants, Oecophylla longinoda Latreille (Hymenoptera: Formicidae) in Cashew Farming Systems in Tanzania - Nene, Wilson; Rwegasira, Gration (European Journal of Applied Sciences, 2026)
The African Weaver ant Oecophylla longinoda holds a potential of being a vital component in Integrated Pest Management (IPM) programs. However, its exploitation in cashew production systems in Tanzania which relies heavily on the use of synthetic insecticides such as Lambda cyhalothrin for the control of cashew bugs (Helopeltis spp.) had been uncertain. This study examined the possibility of O. longinoda rebounding back after spraying Lamda cyhalothrin to control insect pests during cashew fruiting season. The population abundance of O. longinoda and their predation efficiency on Helopeltis spp was determined. The study findings suggest that two to three spraying regimes of the insecticide significantly (P<0.001) reduces O. longinoda population abundances. The average O. longinoda population declined from a range of 201-500 (average 350.5 insects) per cashew tree to 21-50 (average 35.5 insects) per tree. However, we recorded a quick recovery of O. longinoda population of up to >500 insects per tree (score index 5) when favourable conditions were restored immediately after the fruiting season. On predation efficiency, O. longidoda significantly (P<0.001) performed equally to Lambda cyhalothrine in reducing Helopeltis spp. Thus, under suitable conditions, O. longinoda has ability to quickly build up to high populations and adequately suppresses the cashew pests. Conclusively, the present study indicated that, O. longinoda as the predator holds great potential in transforming from conventional to organic cashew production system in Tanzania.